Tapetal 3-Ketoacyl-Coenzyme A Synthases Are Involved in Pollen Coat Lipid Accumulation for Pollen-Stigma Interaction in Arabidopsis - Zhang, Zaibao; Zhan, Huadong; Lu, Jieyang; Xiong, Shuangxi; Yang, Naiying; Yuan, Hongyu; Yang, Zhong-Nan (Frontiers in Plant Science, 2021)
Pollen coat lipids form an outer barrier to protect pollen itself and play essential roles in pollen-stigma interaction. However, the precise molecular mechanisms underlying pollen coat lipids production, deposition, regulation and function during anther development remain largely elusive. 3-ketoacyl-coenzyme A synthases (KCS) are involved in fatty acid elongation or very long chain fatty acid (VLCFA) synthesis. Here, we identified six members of Arabidopsis KCS family expressed in anther. Of them, KCS7, KCS15 and KCS21 expressed in tapetal cells at anther stages 8-10. Further analysis demonstrated that they act downstream of Male sterility1 (MS1), a regulator for late tapetum development. The kcs7/15/21 triple-mutant is fertile. Both cellular observation and lipid staining showed pollen coat lipid was decreased in triple mutant. After landing on stigma, the wild-type pollen grains were hydrated in about 5 min while the triple mutant pollen took about 10 min to hydrate. Pollen tube growth of the triple mutant was also delayed. These results demonstrate the tapetum localized KCS proteins are involved in pollen coat lipid accumulation, and reveal the roles of tapetal-derived pollen coat lipid for pollen-stigma interaction.